Analisis Pengaruh Indeks Pembangunan Manusia, Tenaga Kerja, dan Pendapatan Asli Daerah terhadap Pertumbuhan Ekonomi di Kabupaten Karanganyar Tahun 2008-2021 - Firsta Ayu Fitria Asmoro; Maulidyah Indira Hasmarini; Hanif Fakhruddin (Universitas Batanghari Jambi, 2022)
A country's economic development success is largely based on its economic growth. The human development index, labor, and local revenue are some of the indicators used to influence economic growth. This study aims to examine the factors that influence Karanganyar Regency's economic growth from 2008 to 2021. With the assistance of Microsoft Excel 2016, the time series data for 14 years are analyzed using multiple linear equations (multiple regression), and the data are processed using Eviews 12 with a significance level of 5%. Secondary data were obtained from the Republic of Indonesia's Ministry of Finance and the Central Statistics Agency of Karanganyar Regency. The study reveals that the Human Development Index and Regional Original Income have a significant impact on Economic Growth, whereas Labor does not.